Vrouwen werkzaam in de zeeuwse oesterteelt. Gebruikt voor de Nationale Tentoonstelling van Vrouwenarbeid
Vrouwen werkzaam in de zeeuwse oesterteelt. Gebruikt voor de Nationale Tentoonstelling van Vrouwenarbeid.